Effectiveness of wetland interpretation in affecting school children's attitude towards scratching of trees - M., Roslina; Mariapan, Manohar; Abdul Malek, Ismail Adnan; Aziz, Azlizam; Ramlan, Mohd Aswad (Universiti Putra Malaysia Press, 2013)
Scratching or carving on trees by visitors is a common depreciative behaviour in most recreational forest. Besides spoiling the tree's beauty, damaging its wood, causing infection, thwarting tree's growth or even causing its death, scratch marks on trees will potentially make visitors feel angry and uneasy. Wetlands Environmental Interpretation Program (WEIP) was designed by the Forest Research Institute of Malaysia (FRIM) to tackle this problem. About 72 fifth graders of two approximately similar classes from a National Primary School in FRIM were participants of an experiment. The effects of WEIP on the children's attitude towards depreciative behaviour were investigated. A self-administered questionnaire was given in situ to both the intervention and control groups. The respondents' behaviours were monitored for depreciative behaviours. The results revealed that interpretive learning experiences positively affected the school children's attitude towards scratching on trees. The message conveyed through environmental interpretative learning experiences could help resource managers in curtailing depreciative behaviours by influencing human attitude on the negative acts on flora, fauna, human and the environment.